Contemporary learning techniques for healthcare professionals: A narrative review - Pandit, Anand S. (Frontiers in Education, 2022)
Background As medical knowledge continues to expand at an accelerated rate, healthcare professionals face a significant challenge in remaining up-to-date. The goal of this narrative review was to present evidence-based learning strategies that could aid postgraduate clinical education. Design Articles were sought for using PubMed, Ovid, PsychINFO, ERIC databases and only included if relevant to the review objective. Results A total of 103 articles, chapters, and books were used to compose this narrative review. An additional 135 articles and chapters were examined in full for context. The review is divided into two sections: (1) strategies that can help foster a learning mind-set; and (2) high-yield practical tools that are effective in formal or informal learning domains. Conclusion Individual learning is a cornerstone of clinical performance, which influences the quality of care that one can deliver. This review offers a comprehensive set of learning tools for individuals across a variety of settings.